Productivity Enhancement by Re-Perforation in Abu-Attifel Oil Field -Libya: A Case Study - H. El-Sahati , Ibrahim; Amir, Naji; A. Mahdi, Hameeda (Scientific Journal of University of Benghazi, 2024)
The Libyan National Oil Corporation (NOC) announced a strategic plan at the beginning of 2023 to increase the level of oil production to two million barrels per day. Companies operating in the oil sector have, in turn, started implementing NOC's plan to increase recovery rates from the fields they operate. Mellitah Oil and Gas B.V. Company, Libya branch, started developing measures to enhance production in the Abu-Attifel Oil field. The company sought to enhance the productivity of the two wells, A1 and A3, located in the A100 concession, from the upper Nubian Sandstone reservoir using the Re-perforation technique, as the level of production from these two wells had decreased due to scale formation caused by the accompanying water during production and high temperatures, which led to closing some of perforation intervals. In February 2024, the company succeeded in increasing oil production by 976 STB/D in the A1/A100 well and by 557 STB/D in the A3/A100 well, compared to late 2023 levels, which reflecting the efficacy of the Re-perforation technique in mitigating scale-related issues and optimizing reservoir performance.